West Nile Fever in the Rostov Region: Ecological and Epidemiological Peculiarities of the Outbreak in 2010 - E. A. Moskvitina; M. V. Zabashta; N. L. Pichurina; I. V. Orekhov; Yu. M. Lomov; V. I. Adamenko; D. A. Feronov; A. V. Zabashta; L. M. Verkina; E. V. Kovalev; G. V. Aidinov; M. M. Shvager; et al. (Проблемы особо опасных инфекций, 2011)
This paper describes the outbreak of West Nile fever in the Rostov Region in 2010 and evaluates its ecological and epidemiological peculiarities. From 15th of July till 22nd of September 2010, detected were the 64 cases (1, 4800/0000) of the disease, which were characterized by vector-born mechanism of transmission. Peak of morbidity coincided with mass breeding of Culicidae, increase in the number of Culex mosquitoes, and reoccurring growth of Aedes mosquito population. Diffuse type of the epidemiological process, higher rates of the cases among urbanites, infected in the country-side area, were the characteristic features of that outbreak. West Nile virus antigen was detected by means of IFA in samples taken from An. maculipennis and Cx. pipiens mosquitoes, wild and synanthropic birds, Rh. rossicus ticks, house and wood mice, which facilitates identification of the core factors for the agent circulation and West Nile fever natural focus formation.